Понуда за закључење уговора у пројекту грађанске кодификације Републике Македоније - Дабовиќ Анастасовска, Јадранка, Гавриловиќ, Ненад (Удружење правника у привреди Србије, 2017)
In this paper, the authors deal with the issue of legal regulation of the offer for conclusion of a contract in the project of the third book of the Civil Code of the Republic of Macedonia concerning the law on obligations. Individually reviewed are the reforms of rules of the offer concerning the notion of an offer, the elements of an offer and those on the (ir)revocability of an offer. During the discussion the paper sets out both the rules established by the 2008 amendments to the Macedonian Law of Obligations and the new proposed rules of the codification project. The discussion of the authors demonstrates that the proposed solutions are based on established legal traditions while they also mirror modern solutions of international and European legal sources and projects of contract law.
Offer for conclusion of a contract in the civil law codification project of the Republic of Macedonia
Keywords: contract, offer, offer’s elements, (ir)revocability of offers, reform